Enhancing Fourth-Grade Students’ Creative Thinking in Fictional Narrative Writing Through Project-Based Learning - Ngainul Faidah; Gusti Yarmi; Indra Jaya (MASI Mandiri Edukasi, 2025)
This study was conducted to address the lack of creative thinking skills in writing fictional narrative texts among fourth-grade students at SDN Jurang Mangu Timur 03 in Banten, Indonesia. The issue was evident in their low performance across the indicators of fluency, flexibility, originality, and elaboration. To overcome this challenge, the Project-Based Learning (PjBL) model was implemented. The research adopted a Classroom Action Research design with three cycles, each consisting of planning, implementation, observation, and reflection phases. A total of 29 fourth-grade students participated in the study. The results showed a gradual and significant improvement in students’ creative thinking abilities: only 10% of students scored ≥70 in the pre-cycle, which increased to 45% in Cycle 1, 62% in Cycle 2, and 86% in Cycle 3. These findings indicate that the PjBL model effectively enhanced students' creative thinking skills throughout the intervention cycles.